Latin American novels of the Conquest : reinventing the New World - López, Kimberle S. (University of Missouri Press, 2002)
"The fictionalized explorers and conquistadors represented in this corpus all identify with certain aspects of Amerindian culture - significantly, those elements that are most distinct from European culture, such as cannibalism and human sacrifice - but also feel the need to distance themselves from these "others" in order to protect their own European cultural identity. In most cases, the conquistadors themselves are represented as outsiders within the enterprise of imperialism, due to ethnic, religious, or sexual differences from the norm. This representation turns the gaze inward toward the "other" within European culture, underscoring the complex origins of Latin American cultures in the violent encounter between the Amerindians and the conquistadors." "By examining these issues, Lopez's Latin American Novels of the Conquest illuminates the ways in which Latin American novelists used their literary imaginations to embody their ambivalence regarding their own transcultural heritage as children of both the colonized and the colonizer."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved